Significance and Determinants of Plasma Apelin in Patients With Obstructive Hypertrophic Cardiomyopathy - Yang, Chengzhi; Zhang, Changlin; Jia, Ruofei; Qiao, Shubin; Yuan, Jiansong; Jin, Zening (Frontiers in Cardiovascular Medicine, 2022)
Background：Recent studies suggest apelin has multiple protective effects in some cardiovascular diseases. However, there are few data concerning apelin levels in patients with obstructive hypertrophic cardiomyopathy (OHCM) or the relationship between apelin levels and severity of OHCM. Methods: We studied 88 patients with OHCM and 32 control subjects with matched age and sex distribution. Complete medical history was collected and related examinations were performed. Cardiac magnetic resonance (CMR) and echocardiography were employed to characterize cardiac morphology and function. Plasma apelin was measured by enzyme-linked immunosorbent assay (ELISA). Results: Plasma apelin levels were significantly lower in patients with OHCM than those in control subjects (96.6 ± 34.3 versus 169.4 ± 62.5 μg /L, p <0.001). When patients with OHCM were divided into two groups according to the mean value of plasma apelin, patients with lower apelin levels (plasma apelin≤96.6μg /L) had greater septal wall thickness (SWT; 25.6 ± 5.5 versus 23.2 ± 4.3 mm, p = 0.035) and less right ventricular end-diastolic diameter (RVEDD; 20.4 ± 3.3 versus 23.0 ± 3.6 mm, p = 0.001). Consistently, plasma apelin levels were inversely correlated with SWT (r = -0.334, p = 0.002) and positively correlated with RVEDD (r = 0.368, p <0.001). Besides, plasma apelin levels were inversely correlated with Ln (NT-proBNP) (r = -0.307, p = 0.008) and positively correlated with body mass index (BMI; r = 0.287, p = 0.008). On multivariate analysis, the SWT was independently associated with decreasing plasma apelin, while the RVEDD was independently associated with increasing plasma apelin. Conclusions: Plasma apelin levels are reduced in patients with OHCM. The apelin levels are inversely related to SWT and positively related to RVEDD